Implementation of individual placement and support in a first‐episode psychosis unit: A new way of working. (12th May 2020) - Hillborg, Helene; Bergmark, Magnus; Bejerholm, Ulrika
Abstract: The aim of this study is to explore the IPS implementation process in a first‐episode psychosis (FEP) mental health service team in Sweden. More specifically, the study explores how integration processes and critical situations are perceived over time by team members who originated from two diverse welfare organizations. A serial interview design was used (initially, at 6 and 12 months) to describe experiences of 16 team members. Material was analyzed using a constant comparison grounded theory approach. Team members dealt with the ambivalence of sharing mental health information, and whether the new way of working was a risk or benefit for users. They gradually learned new perspectives and knowledge, built trust and shared common views. After a year, the team workload perceived reduced and became person‐centred. Some members described remaining unclear roles and requested further support. Negotiated goals for integration and early knowledge transfer are critical. Organizational change and trusting team relationships have to be facilitated. Anticipated gains of integration should be clearly described and discussed early on, and continuous support for sustainability should be considered. This study confirmed the importance and potential of integrating IPS into FEP teams.